P471 Association of vedolizumab levels with clinical and biochemical markers of inflammation during maintenance therapy in inflammatory bowel disease. (25th January 2019) - Plevris, N; Jones, G R; Jenkinson, P W; Chuah, C S; Lyons, M; Merchant, L M; Pattenden, R J; Arnott, I D; Lees, C W
Abstract: Background: The role of TDM in the context of vedolizumab therapy remains unclear. Initial studies have shown a relationship between post induction levels andlong-term outcomes. However, the clinical utility of measuring levels during maintenance treatment remains to be elucidated. Therefore, we aimed to establish the relationship between trough vedolizumab levels and clinical remission, biochemical remission, and faecal biomarker remission during maintenance therapy. Methods: We performed a prospective cross-sectional service evaluation of IBD patients receiving maintenance vedolizumab. All patients had received a minimum of 12 weeks therapy following standard induction (0, 2, 6 ± 10 week dosing). Over a 16 week period, data on clinical activity (HBI or Partial Mayo score), CRP, vedolizumab levels and faecal calprotectin were collected at patients infusions. Clinical remission was defined as HBI <5 or partial Mayo <2; biochemical remission as CRP <5 g/l; and faecal biomarker remission as faecal calprotectin (FC) <250 µg/g. Vedolizumab levels were processed using the Immundiagnostik monitor ELISA. Results: Seventy-three patients (30 UC, 43 CD; median age 36 years [IQR 29–56]) fulfilled inclusion criteria and had vedolizumab levels matched with clinical activity scores, CRP and faecal calprotectin. Median disease duration was 12 years (IQR 7–19) with a median vedolizumab duration of 1.6 years (IQR 0.8–2.2). 20.5% of the cohort were receiving a concomitant immunomodulator. The majority of patients had detectable levels ( n = 71/73, 97.3%) with a median vedolizumab level of 10.6 µg/ml (IQR 7.9–16.1). No significant difference was observed in median levels between UC and CD patients (11.1 µg/ml vs. 10.4 µg/ml, p = 0.54). Individuals on 4-weekly therapy had higher median levels than those on 8- weekly (16.1 µg/ml vs. 10.4 µg/ml, p = 0.02). A correlation was observed between vedolizumab levels and albumin (Spearman's r = 0.25, p = 0.03) as well as BMI (Spearman's r = −0.40, p < 0.01). Clinical remission, biochemical remission and faecal biomarker remission was present in 78.1%, 71.2% and 67.1%, respectively. No difference was observed in vedolizumab levels in patients in clinical remission, biochemical remission or with faecal biomarker remission (Figure 1). Area under the ROC curve for predicting clinical remission, biochemical remission and biomarker remission was 0.55 ( p = 0.54), 0.63 ( p = 0.08) and 0.53 ( p = 0.66), respectively. Conclusions: Vedolizumab trough levels are not associated with outcomes during maintenance therapy.